HOW ATTITUDE TOWARD BEHAVIOR, PERCEIVED BEHAVIORAL CONTROL, PERSONAL NORM, AND PRO-ENVIRONMENTAL IDENTITY AFFECT WASTE REDUCTION BEHAVIOR AMONG FEMALE WORKERS - Solekah, Nihayatu Aslamatis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
This study aims to determine the Waste Reduction Behavior (WRB) of female workers by developing a theory of planned behavior with Attitude toward Behavior (AtB) and Perceived Behavioral Control (PBC) variables, value belief norm theory with Personal Norm (PN) variable, and contextual consistency theory with Pro-environmental Identity (PEI) variable. The population in this study are female lecturers at universities around Malang Raya. It employs a purposive sampling with the criteria of female lecturers and a minimum master's degree with at least one year of work. The study is participated by 128 respondents. The results show that AtB and PBC do not bring about any effect on IRB, but PBC affects WRB. PN and PEI affect IRB, but PEI does not affect WRB. Meanwhile, IRB affects WRB. The study results imply that the identity of pro-environmental behavior by waste reduction among women workers has not reached the stage of factual behavior yet, in contrast to their perceived behavioral control in the form of difficulties and conveniences that directly affect their waste reduction behavior.